2003
DOI: 10.1046/j.1526-0968.2003.00094.x
|View full text |Cite
|
Sign up to set email alerts
|

The Change in Renal Replacement Therapy on Acute Renal Failure in a General Intensive Care Unit in a University Hospital and its Clinical Efficacy: A Japanese Experience

Abstract: The aim of our study was to examine renal replacement therapies (RRT) that have been used for acute renal failure (ARF) in our intensive care unit (ICU) patients and to compare their outcomes. Sixteen patients who underwent intermittent hemodialysis (IHD), 14 patients who underwent continuous hemofiltration (CHF) in combination with IHD (CHF + IHD), and 38 patients who underwent continuous hemodiafiltration (CHDF) were evaluated. Regarding the effects of blood purification on hemodynamics and renal function, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…Therefore, when hypercytokinemia is suspected in critically ill patients with AKI with symptoms of high fever and low blood pressure prior to treatment, the use of PMMA membrane might be beneficial. Our results indicated that in RRT, the selection of an appropriate hemofilter is also crucial for modulating humoral mediators, because the efficacy of cytokine removal depends on the type of hemofilter used; this has also been indicated by several other researchers (25–27).…”
Section: Discussionsupporting
confidence: 68%
“…Therefore, when hypercytokinemia is suspected in critically ill patients with AKI with symptoms of high fever and low blood pressure prior to treatment, the use of PMMA membrane might be beneficial. Our results indicated that in RRT, the selection of an appropriate hemofilter is also crucial for modulating humoral mediators, because the efficacy of cytokine removal depends on the type of hemofilter used; this has also been indicated by several other researchers (25–27).…”
Section: Discussionsupporting
confidence: 68%
“…These factors include advanced age, male gender, prolonged hospital stay, hepatic or biliary tract diseases, prolonged prothrombin time, hypotension, metabolic acidosis, sepsis, coma, need of vasoactive drugs, respiratory distress or need for mechanical ventilation, need for dialysis, use of vasoactive drugs, high levels of serum creatinine, oliguria and delayed consultation by the nephrologists [3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…10 Over the past years, several studies have been performed with the aim of identifying prognostic factors and predicting the outcomes for critically ill patients with ARF admitted to intensive care units (ICUs). 7,[10][11][12][13] The risk factors for death identifi ed in previous studies were advanced age, male gender, prolonged hospital stay, hepatic or biliary tract diseases, hematological dysfunction, hypotension, shock, coma, need for vasoactive drugs, respiratory distress or need for mechanical ventilation, sepsis, need for dialytic treatment, high levels of creatinine, oliguria and delayed consultation with a nephrologist. 6,8,11,12,[14][15][16] Better knowledge of factors associated with a bad prognosis in ARF cases is very important for improving prevention and treatment, especially among critically ill patients.…”
Section: Introductionmentioning
confidence: 99%
“…4,6,[8][9][10][11][12][13][14][15][16] The present study had the aim of investigating the risk factors for death among critically ill patients with ARF admitted to an ICU in northeastern Brazil. Knowledge of these factors will be important for adopting preventive measures and more adequate treatment that could decrease mortality rates.…”
Section: Introductionmentioning
confidence: 99%